A Pure CMOS Stack Electrostatic Micromirror Featuring Simplified Fabrication and Stress-Adjusted Modeling - Wenhao Chen; Hadi Tavakkoli; Bin Zhao; Maojie Zhang; Wibool Piyawattanametha; Yi-Kuen Lee (My University, 2025)
We report a pure CMOS stack-made comb-actuated electrostatic micromirror for non-resonant scanning using a standard 0.18 μm 1-polysilicon 6-metal CMOS foundry process without complex post-processing steps. The staggered vertical combs are formed by different metal layers to provide a nonlinear electrostatic torque, enabling the device to achieve a 12.4° optical scan angle under 70V with a mirror size of 0.4×0.4 mm2. Considering CMOS process-induced stress, a modified theoretical model of the comb actuators agrees with experimental data, which gives a guideline for the design optimization of non-resonant CMOS-MEMS mirrors. This innovative integration of comb-drive actuator and mirror structure within the limited thickness of the standard CMOS stack (11 μm) and improved manufacturability boost a new generation of compact, high-performance optical MEMS devices.
Keywords: Advanced MEMS and NEMS Technologies; Advanced Sensor and Energy Harvesting Materials; Advancements in Semiconductor Devices and Circuit Design